A MILLENNIAL-SCALE RECONSTRUCTION OF SPRUCE BUDWORM ABUNDANCE IN SAGUENAY, QUEEBEC, CANADA - Simard I.; Morin H.; Lavoie C. (My University, 2006)
A high-resolution macrofossil analysis was conducted to reconstruct spruce budworm abundance in an 8600-year-old mire in Saguenay, QuEbec, Canada. Abundant spruce budworm (Choristoneura fumiferana [Clem.]) faeces recovered in the peat profile suggested endemic and epidemic presence of the insect in the study site since 8240 cal. BP. Important variations in the abundance of faeces were observed, and two exceptional periods of insect activity were delineated, from 6815 to 6480 cal. BP and during the twentieth century. Lepidoptera head capsules were also found in the Lac des Ilets peat profile. They were less abundant and more altered than spruce budworm faeces, but they offered complementary information on insect activity. The long-term perspective achieved with this macrofossil analysis strongly suggests that intense periods of spruce budworm activity were rare events during the Holocene.
Keywords: INSECT FAECES; LEPIDOPTERA HEAD CAPSULE; MACROFOSSIL ANALYSIS; MIRE; OUTBREAK; SPRUCE BUDWORM; QUEBEC; CANADA; HOLOCENE; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен